2007
DOI: 10.1007/s10396-006-0127-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of left ventricular diastolic function using color kinesis

Abstract: We conclude that the analysis of diastolic CK by using ICK software is a useful technique that can be applied to quantitative evaluation of LV global diastolic function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Color kinesis (CK) is a real-time echocardiographic technique based on acoustic quantification that yields regional and global information on the magnitude and timing of LV wall motion by tracking and color-encoding endocardial motion throughout the cardiac cycle [18][19][20][21]. We previously reported that the analysis of diastolic CK is a useful method for quantitative evaluation of LV diastolic function and detecting delayed LV relaxation [22,23]. The aim of this study is to investigate the relationship between plasma BNP levels and LV diastolic function by using diastolic CK imaging.…”
Section: Introductionmentioning
confidence: 99%
“…Color kinesis (CK) is a real-time echocardiographic technique based on acoustic quantification that yields regional and global information on the magnitude and timing of LV wall motion by tracking and color-encoding endocardial motion throughout the cardiac cycle [18][19][20][21]. We previously reported that the analysis of diastolic CK is a useful method for quantitative evaluation of LV diastolic function and detecting delayed LV relaxation [22,23]. The aim of this study is to investigate the relationship between plasma BNP levels and LV diastolic function by using diastolic CK imaging.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, the mean CK-DI for six LV segments was 70.6% in 20 healthy subjects (mean age: 30 ± 18 years), indicating that approximately 70% of maximum LV fi lling occurs during the fi rst 30% of the diastolic fi lling time in normal subjects. 11 In addition, the CK-DI of 30 patients (mean age: 67 ± 11 years) with normal LV systolic function and impaired relaxation was 50.5%. Based on these fi ndings, we reported that advanced diastolic dysfunction leads to a decrease in mean CK-DI even if systolic function remains normal.…”
Section: Ck-diastolic Index As Parameter Of Diastolic Functionmentioning
confidence: 99%
“…We believe that the mean CK-DI represents a quantitative index of LV diastolic function that does not depend on LV volume change. 11 Furthermore, diastolic function may be improved by medical treatment in patients with heart failure. Figure 6 illustrates an example of a patient who improved with treatment.…”
Section: Ck-diastolic Index As Parameter Of Diastolic Functionmentioning
confidence: 99%
“…Two of these techniques are based on analyzing ultrasound radiofrequency (RF) signals [5][6][7][8][9][10][11][12][13][14][15][16][17]. The first method known as acoustic quantification is based on the detection of the interface between the tissue and the blood in each image.…”
Section: Introductionmentioning
confidence: 99%
“…Synthesized color-coded images (color kinesis) are provided using this method to display the timing and magnitude of endocardial wall motion over time, either during the systolic phase or during the diastolic phase [5][6][7][8][9][10][11]. The various quantitative indices obtained from these synthesized images are proposed for assessment of RWM of LV [6][7][8][9][10][11]. However, this method is very dependent on the signal to noise ratio of RF signal.…”
Section: Introductionmentioning
confidence: 99%